Handbook of research on small and medium enterprises in developing countries - Ahmad, Noor Hazlina; Ramayah, T.; Abdul Halim, Hasliza; Rahman, Syed Abidur (IGI Global, 2017)
Smaller companies are abundant in the business realm and outnumber large companies by a wide margin. Understanding the inner workings of small businesses offers benefits to the consumers and the economy.The Handbook of Research on Small and Medium Enterprises in Developing Countries is an essential handbook for the latest research on the intentions, performance, and application models of independent firms.Featuring exhaustive coverage on a broad range of topics such as green IT, entrepreneurial ventures, and social capital, this publication is ideally designed for researchers, academicians, and practitioners seeking current research on the different opportunities and challenges in relation to this specific sector of business around the globe.